An Approach to Motivate and Improve Learning in Beginning Engineering Students Beginning Engineering Students A comparative experimentation in robotic arm control using robotic arm control using Matlab and Arduino. (LACCEI, 2024)
Abstract- This article develops the simulation of the control of a robotic arm of articulated structure with rotary movement and linear displacement as a means of learning and motivation for beginner students in engineering. For which Matlab were used, Arduino software and graphical interface of the Coppeliasim program were used. In Matlab, specifically in the Simulink environment together with the SYMSCAPE Multibuerpo Link complement, the functions of GUI developed the control of the robotic arm articulated with different values in the angles of the joints for their subsequent motion simulation, while in Arduino 1 the interface Coppeliasim was used to have the visualization of what has been done since Arduino 1 has not had the option of showing graphics, so this support program was necessary to achieve the comparison. The simulation results are presented through a comparative data table where software is evaluated to determine the benefits in the teaching learning process.